Effect of alpha Lipoic Acid on Some Reproductive Hormones in Adult Male Wister Rats Exposed to Hydrogen Peroxide - Mohammed Salih Alwan; Baraa Najim Al-Okialy (Kufa Journal for Veterinary Medical Sciences, 2019)
The present study was aimed to investigate the role of alpha lipoic acid (ALA) on reproductive hormonal profile in adult male Wister rats treated with hydrogen Peroxide. Forty adult male rats were divided randomly into four equal groups (10 rats /group) and were handled daily as follows for 56 days: Control group (C) were intubated distilled water and received tap water ; group T1 were intubated 60mg/kg B.W of ALA and received tap water; group T2 administered hydrogen peroxide H2O2 in tap water at concentration of 0.05%, while group T3 were intubated 60mg/kg B.W of ALA and received ordinary tap water containing 0.05% H2O2. Blood samples were collected at 0, 28 and 56 days of the experimental periods for measurement of serum follicular stimulation hormone (FSH), lutelizing hormone (LH) and testosterone (T) concentrations. The results revealed that group T2 showed a significant decrease in FSH and testosterone concentrations. While there were significant increase in previous parameters in T3 group compared to T2 group. Whereas, rats in group T3 shows significant improvement in above serum hormonal profile by repairing role of alpha lipoic acid against hydrogen peroxide in (group T2). In conclusion, alpha lipoic acid mitigated the deleterious effect of that-induced H2O2 induced pituitary-testicular dysfunction through antioxidant mechanism by free radical scavenging properties